2009
DOI: 10.1068/b34111t
|View full text |Cite
|
Sign up to set email alerts
|

Delineating urban housing submarkets with fuzzy clustering

Abstract: It has long been argued that the housing market is spatially compartmentalized within a metropolitan area. The argument has important implications for explaining how the housing market works—should the status quo be seen as an equilibrium state? Or if no equilibrium is reached, how do loosely interlaced submarkets function both independently and interdependently? We note that the body of literature has leaned toward testing the distinctiveness of housing submarkets given a priori housing submarkets. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…Jones et al 2012). Indeed, the data in Table 1 reinforce the idea that the spatiality of housing search can best be expressed through a multi-layered, non-nested approach to housing submarkets where there is a relationship between income constraints, property types and spatial search patterns (Watkins, 2001;Hwang and Thill, 2009). This proposition is explored in more detail in the next section.…”
Section: Figure 5 -Price Criteria Entered By Draw-a-search Usersmentioning
confidence: 64%
“…Jones et al 2012). Indeed, the data in Table 1 reinforce the idea that the spatiality of housing search can best be expressed through a multi-layered, non-nested approach to housing submarkets where there is a relationship between income constraints, property types and spatial search patterns (Watkins, 2001;Hwang and Thill, 2009). This proposition is explored in more detail in the next section.…”
Section: Figure 5 -Price Criteria Entered By Draw-a-search Usersmentioning
confidence: 64%
“…Research has shown that crime has an impact on housing prices (Thaler, 1978;Rizzo, 1979;Buck et al, 1991;Bowes and Ihlanfeldt, 2001;Lynch and Rasmussen, 2001;Munroe, 2007;Hwang and Thill, 2009;Wilhelmsson, 2011, 2012). Yet this evidence is based on sales of properties located in large urban areas.…”
Section: Introductionmentioning
confidence: 93%
“…The distance to central business districts (CBDs) has been critical for housing choice and prices with the "access/space trade-off" model [44,45] depicting a trade-off between the reduced land cost of suburban areas and the increasing commuting cost of travel and transportation to CBDs. Hwang and Thill (2011) found an association between job accessibility and housing price by measurement of travel-time-based job accessibility in Seattle [46]. There have been, however, contradictory debates regarding the model due to the assumption limitation, such as monocentric urban structures, the isotropic condition of terrain, and perfect competition markets [41,47,48].…”
Section: Hedonic Price Modelmentioning
confidence: 99%